2017
DOI: 10.1021/acs.chemmater.7b01873
|View full text |Cite
|
Sign up to set email alerts
|

Precise Engineering of Nanocrystal Shells via Colloidal Atomic Layer Deposition

Abstract: We present a general strategy for a facile synthesis of complex multifunctional nanoscale materials via colloidal atomic layer deposition (c-ALD). The c-ALD technique is based on self-limiting half-reactions of ionic precursors on the surface of a nanocrystal (NC) occurring at room temperature. Using this technique, uniform layers of CdS and ZnS semiconductor shells were epitaxially grown on CdSe semiconductor cores with different shell combinations, leading to the precise control of the optical properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…Ambient sunlight, or even a white‐light lamp irradiation, leads to high QYs by eliminating defects in the NPLs. We have also demonstrated that depositing alternating shell layers of ZnS, CdS, and Cd x Zn 1‒ x S creates an additional degree of freedom for modulating the optoelectronic properties of NPLs, as we recently showed for spherical CdSe quantum dots . We have revealed theoretically the atomistic mechanisms that govern shell growth and thus the optical changes observed experimentally.…”
Section: Resultssupporting
confidence: 58%
“…Ambient sunlight, or even a white‐light lamp irradiation, leads to high QYs by eliminating defects in the NPLs. We have also demonstrated that depositing alternating shell layers of ZnS, CdS, and Cd x Zn 1‒ x S creates an additional degree of freedom for modulating the optoelectronic properties of NPLs, as we recently showed for spherical CdSe quantum dots . We have revealed theoretically the atomistic mechanisms that govern shell growth and thus the optical changes observed experimentally.…”
Section: Resultssupporting
confidence: 58%
“…CsPbX 3 (X = Cl, Br, and I) perovskite nanocrystals (NCs) are one of the most competitive candidates for the next-generation illumination and display applications because of their extraordinary optoelectronic properties. As an alternative to well-developed semiconductor quantum dots (QDs), CsPbX 3 NCs show higher photoluminescence quantum yields (PLQYs) up to 100%, narrower full-width-at-half-maximum (fwhm) down to 20 nm, and the tunable PL emission position covering the entire visible spectra. Unlike conventional semiconductor QDs, CsPbX 3 NCs usually possess cube morphology with average size over 10 nm beyond the diameter of Bohr exciton, which makes it hardly possible to perform accurate control of PL emission by tailoring their size. , The common strategy to achieve emission control of CsPbX 3 NCs is anion exchange, which refers to the exchange of halide ions in the as-prepared CsPbX 3 NCs to realize broad halide composition on the basis of their high ion mobility. However, the conventional anion-exchange routes suffer from complicated pretreatment, inert reaction environment, excess ligand-induced NC degradation, and non-quantitative halide-exchange process, usually causing unpredictable PL shift rather than specific emission control. , Although droplet-based microfluidic platform, , assembly-induced contraction strategy, and thermodynamic size control method have successfully achieved good emission control of perovskite NCs in limited spectral range, the continuous emission adjustment in the full visible spectra with the interval of 1 nm is still challenging.…”
Section: Introductionmentioning
confidence: 99%
“…[3] To date,v arious strategies have been developed for the synthesis of metal sulfide core-shell structures including the thermal-cycling coupled single precursor, [4] hot-injection method, [5] successive ion layer adhesion and reaction, [6] and colloidal atomic layer deposition. [7] These methods are majorly dependent on the epitaxial growth process.L attice match between the core and shell is the prerequisite. [8] Furthermore,o rganic solvents are often involved during the synthesis,t hus yielding core-shell structures capped with organic ligands that are not suitable for photocatalytic applications.M etal sulfides such as CdS have been generally regarded as one of the most promising candidates for photocatalytic H 2 production owing to their suitable bandgap structures for visible light utilization; [9] however,i t generally suffers from low photostability and photocatalytic reaction kinetics for hydrogen production, because the water oxidation is too slow to efficiently consume the photogenerated charges.F or ap ractical photocatalysis system, cocatalysts are absolutely required to promote the charge separation and facilitate the surface redox reactions.…”
Section: Introductionmentioning
confidence: 99%